Stepping up Effort to Enlightenment in the Novel Graceland (2004) by Chris Abani - Ilma Fitriani; Leni Marlina (Universitas Negeri Padang, 2019)
This thesis is the analysis of a novel which written by Chris Abani entitled Graceland (2004). It explores the issue of step up efforts to enlightenment which reflected by the main character. It is also intended to find out the contribution of fictional devices such as character, plot (conflict), and setting in revealing the issue of efforts to enlightenment. This analysis is related to the concept of life instinct which self-awareness by Sigmund Freud that is supported by the text-based and context-based interpretation. The result of this analysis shows about the way the main character effort to enlightenment in dealing with any situation in his life by building self-awareness, gaining thinking skill and having vocational skill.